Resistência ao cisalhamento de diferentes sistemas adesivos no esmalte dental - Paradella, Thaís Cachuté [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The purpose of this study was to evaluate in vitro three adhesive systems: a total etch single-component (GI Prime & Bond 2.1 ), a self-etching primer (GII Clearfil SE Bond) and a self-etching adhesive (GIII One Up Bond F), through shear bond strength on enamel of human teeth, evaluating the type of fracture through stereomicroscopy. Thirty premolars, kept in 0.5% chloramines solution received cuts in mesium-distal sense and had their ena mel surfaces prepared. They were randomly assigned to three experimental groups (n=20). The adhesive system's area of acting was determined and the adhesive procedures were performed according to the manufactureis instructions. 3mm Z-250 composite resin cylinders were performed. The specimens were kept in distilled water at 370C for 24h, thermocycled for 500 cycles (5ºC-55ºC) and submitted to shear with 0.5mm/min speed. The adhesive resistance mediums were GI 18.13 ± 6.49 MPa, with 55% of resin cohesive fractures; GII 17.12 ± 5.80 MPa with 90% of adhesive fractures and GIII 10.47 ± 3.14 MPa with 85% of adhesive fractures. The data was submitted to Anova and Tukey multiple comparison (5%) statistical analysis. There were no significant differences between Gl and GIl, having GIII significant difference regarding the other groups. The predominant type of fracture (adhesive in GIl) was submitted to SEM and the rupture in the resin-tooth interface was noticeable. lt was concluded that the adhesive system in Gl presented similar shear bond strength to GIl, however with a different type of fracture

O objetivo deste estudo foi avaliar in vitro três sistemas adesivos: um monocomponente com condicionamento ácido prévio (GI Prime & Bond 2.1), um primer autocondicionante (GII Clearfil SE Bond) e um adesivo autocondicionante (GIII One Up Bond F), através da resistência ao cisalhamento no esmalte de dentes humanos, avaliando-se o tipo de fratura por estereomicroscopia. Trinta pré-molares armazenados em solução de cloramina a 0,5% receberam cortes em sentido médio-distal e tiveram suas superfícies de esmalte planificadas. Os espécimes foram aleatoriamente divididos nos três grupos experimentais (n=20). A área de atuação dos adesivos foi delimitada e os procedimentos adesivos realizados conforme recomendações dos fabricantes. Cilindros de resina composta Z-250 de 3mm de diâmetro foram confeccionados. Os espécimes foram armazenados em água destilada a 37°C por 24h, termociclados por 500 ciclos (5°C-55°C) e cisalhados com velocidade de 0,5mm/min. As médias de resistência adesiva foram Gl 18,13 ± 6,49 MPa, com 55% de fraturas coesivas em resina composta; Gll 17,12 ± 5,80 MPa com 90% de fraturas adesivas e Glll 10,47 ± 3,14 MPa com 85% de fraturas adesivas. Os dados foram submetidos à análise estatística ANOVA e comparação múltipla de Tukey (5%), não havendo diferenças significantes entre o Gl e o GIl, tendo o Glll diferença significante em relação aos outros grupos. O tipo de fratura mais predominante (adesiva do GIl) foi submetido à MEV e observou-se a ruptura na interface resina-dente. Concluiu-se que o adesivo do Gl promoveu resistência de valor semelhante ao GII, porém com tipo de fratura diferente
Keywords: Esmalte dentário; Materiais dentários; Adesivos dentarios; Cisalhamento; Dental enamel